Hubungan Antara Status Gizi dan Mobilitas dengan Risiko Terjadinya Dekubitus pada Pasien Stroke di Rumah Sakit Umum Daerah Dr.Moewardi Surakarta - Puspaningrum, Yetiana Valentin, Agus Sudaryanto, S.Kep., Ns., M.Kes, Rina Ambarwati, S.Kep., Ns (2013)
Stroke is a disease that most often lead to disability, especially paralysis of the limbs. In the early phase of stroke symptoms that most often arises is disfagia, anorexia, nausea and vomiting. Immobility and nutrition deficiency can lead to pressure sores. Pressure sores is injury incurred because pressure, especially on the prominent bones result a long bed rest. This study aims to determine the relationship between nutritional status and mobility with the risk of pressure sores in stroke patients in Dr. Moewardi of Surakarta. This research is descriptive correlative with quantitative design. While the research design used a cross-sectional study. The study population was a stroke patient who is hospitalized in the Dr. Moewardi Surakarta hospital in April-May 2013. Total sample as many as 80 patients, using accidental sampling technique. Using a check list of research instruments and observation sheets. Hypothesis testing using Chi-Square. Conclusions of this study are: (1) There is a relationship between nutritional status with risk of pressure sores in stroke patient, (2) There is a relationship between mobility with the risk of developing pressure sores in stroke patients in Dr. Moewardi of Surakarta.